From a local "Erfahrungsgeschichte of Holodomor" to a global history of famines - Penter, Tanja (Contemporary European history, 2018)
In German historiography, the Ukrainian famine has not received adequate attention. A few exceptions exist, such as the 2004 special issue of the journal Osteuropa edited by Gerhard Simon and Rudolf Mark, but no single monograph in the German language nor any research project deals with the Holodomor. Moreover, amongst the broader German public, the Soviet famine of 1932-3 is relatively unknown, despite being one of the great catastrophes in twentieth-century European history and (in terms of its death toll) one of the biggest single crimes of Stalinism. How can this obvious omission on the part of German academic researchers of Stalinism be explained?
Gesehen am 13.12.2018